1999
DOI: 10.1021/bi982945n
|View full text |Cite
|
Sign up to set email alerts
|

Replacements of Basic and Hydroxyl Amino Acids Identify Structurally and Functionally Sensitive Regions of the Mitochondrial Phosphate Transport Protein

Abstract: The mitochondrial phosphate transport protein (PTP) from the yeast Saccharomyces cerevisiae has been expressed in Escherichia coli, purified, and reconstituted. Basic and hydroxyl residues were replaced to identify structurally and functionally important regions in the protein. Physiologically relevant unidirectional transport from extraliposomal (cytosol) pH 6.8 to intraliposomal (matrix) pH 8.0 was assayed. Replacements that affect transport most dramatically are at Lys42 (matrix end of helix A), Thr79 (heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
4
19
0
Order By: Relevance
“…The amount of reconstituted wild-type and mutant proteins varied between 16% and 28% of the added protein, which is similar to values found for other recombinant reconstituted mitochondrial carrier proteins. 17,[22][23][24][25][26][27] For transmembrane α-helices H1, H3 and H5, Figure 2 shows the initial transport rates of 2-oxoglutarate for each recombinant OGC as a percentage of the value for the cysteine-less carrier. The effects of the mutations on the initial transport rate were mapped on the comparative model of OGC ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of reconstituted wild-type and mutant proteins varied between 16% and 28% of the added protein, which is similar to values found for other recombinant reconstituted mitochondrial carrier proteins. 17,[22][23][24][25][26][27] For transmembrane α-helices H1, H3 and H5, Figure 2 shows the initial transport rates of 2-oxoglutarate for each recombinant OGC as a percentage of the value for the cysteine-less carrier. The effects of the mutations on the initial transport rate were mapped on the comparative model of OGC ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The proline residues of the signature motif induce sharp kinks in the odd-numbered α-helices, closing the central pore of the α-helical bundle at the matrix side, whereas the charged residues form a salt bridge network at the bottom of the cavity. 10 Some residues of the signature motif have been shown to be important for function in the ADP/ ATP carrier, [13][14][15] the phosphate carrier 16,17 and the citrate carrier. 18 The structure of the mitochondrial ADP/ATP carrier in the cytoplasmic state is known, 10 but the structural changes required for the translocation of the substrate are not.…”
Section: Introductionmentioning
confidence: 99%
“…Lys 179 and Lys 187 ) that reside within its fourth ␣-helical transmembrane domain (27). These residues FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the CTP was incorporated into liposomes both in the (25,26,27), depicts six transmembrane ␣-helical segments. These segments are connected by five hydrophilic loops.…”
mentioning
confidence: 99%
“…The same P i transport inhibitions by FITC with and without DTT treatment clearly showed that the possible labeling of cysteine residues with FITC (24) was not associated with P i transport inhibition by FITC. This conclusion is supported by the finding that replacement by Ala or Arg of Lys 187 of the yeast carrier, which corresponds to Lys 185 of the bovine carrier, resulted in complete loss of the transport activity (33).…”
Section: Discussionmentioning
confidence: 76%